2020
DOI: 10.21273/horttech04656-20
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Performance of Reduced-risk Fungicides and Biorational Products in Management of Postharvest Botrytis Blight on Bigleaf Hydrangea Cut Flowers

Abstract: Botrytis cinerea is one of the problematic and notorious postharvest pathogens of bigleaf hydrangea (Hydrangea macrophylla) cut flowers. It causes flower blight, leaf blight, and stem rot, reducing the ornamental value (such as longevity, color, and texture) of flowers, ultimately making them unsalable. The objective of this study was to identify effective conventional fungicides and biorational products for botrytis blight management on bigleaf hydrangea cut flowers that can be easily and readily adopted by g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 58 publications
(61 reference statements)
0
4
0
Order By: Relevance
“…Biorational products can be adopted for fungal disease management. These products refer to pesticides of natural origin such as botanicals, minerals, microorganisms, and minimum-risk chemicals that have reduced or no negative effects on the environment or beneficial organisms [49,50]. Biocontrol of powdery mildew was achieved on various hosts, including Trichoderma isolates [23,51], yeasts, mycophagous arthropods, mycolytic bacteria, and additional effective biological agents.…”
Section: Biological Controlmentioning
confidence: 99%
See 3 more Smart Citations
“…Biorational products can be adopted for fungal disease management. These products refer to pesticides of natural origin such as botanicals, minerals, microorganisms, and minimum-risk chemicals that have reduced or no negative effects on the environment or beneficial organisms [49,50]. Biocontrol of powdery mildew was achieved on various hosts, including Trichoderma isolates [23,51], yeasts, mycophagous arthropods, mycolytic bacteria, and additional effective biological agents.…”
Section: Biological Controlmentioning
confidence: 99%
“…It is also suggested that root symbiosis with rhizobia can be used by priming plants with salicylic acid accumulation and defense-gene expression, which is triggered by powdery mildew [23]. However, the downside to certain biological control and biorational products is the limitation of efficacy in wider field conditions [50]. There is also the concern of non-native species posing an ecological risk [47].…”
Section: Biological Controlmentioning
confidence: 99%
See 2 more Smart Citations